Aerospace series. Steel X5CrNiCu 17-4 (1.4542). Air melted. Solution treated and precipitation treated. Sheets and strips. a ? 6 mm. Rm ? 1 070 MPa. (17th January 2023) - British Standards Institution,
No abstract available